Multi-level marketing as a profit mechanism for sales forces Case study Arvea - Bouameur, Aicha; Messaoudi, Khiera (Dirassat Journal Economic Issue, 2023)
This research paper aimed to address the healthy model of multi-level marketing that does not conflict with the ethics and legitimacy of the marketing profession in order to highlight its importance as a mechanism to achieve profits for sales forces in general and those active in Arvea Foundation in Algeria in particular, and the study was determined by an independent variable (multi-level marketing) with its dimensions. The four represented by the elements of the multi-level marketing mix and the dependent variable represented in achieving profits for the selling forces, as the study targeted a sample of 51 sales representatives at Arvea, whose data was processed and analyzed by the 22spss program. The study concluded that there is a direct correlation between multi-level marketing and the achievement of profits for the selling forces through the quality and effectiveness of the elements of its marketing mix that increase the confidence of customers in the products of the institution. to the selling forces to earn their lasting loyalty.